Correlation between SREBP-1c and Prominent Nucleoli Hepatocytes of Type 2 Diabetic Rat Model Induced by Dietylnitrosamine - Wahyuni L Atmadja; Erna Kristiani; Stella Marleen; Veli Sungono; Young Larasati; Kevin Feraldy (Journal of Medicine and Health, 2023)
Type 2 Diabetes Mellitus (T2DM) demonstrates relative risk of cirrhosis towards livercancer. Although the relationship between of type 2 diabetic and cirrhotic toward HCC has beensuggested, the association between SREBP-1c and the number of prominent nucleoli hepatocyteshas not clearly explored. This study aims to prove the correlation between those variables byusing male Wistar rat model given fat diet continued with administration of Streptozotocininjections twice in low dosage and an injection of dietylnitrosamine once a week for 10 weeks. Atweek 16, they were sacrificed, the fresh liver tissue was processed for examining the expressionof SREBP-1c, while the fixative paraffin block was sliced and stained with Hematoxylin Eosin tocount the number of prominent nucleoli hepatocytes. The western blotting result demonstratedincreasing level of SREBP-1c in diabetic rat significantly. The liver sections showed nodulesconsisting of pleomorphic cells, inflammatory cells, and prominent nucleoli hepatocytes. Thecorrelation between level of SREBP-1c and total number of prominent nucleoli hepatocytes wasmeasured with non-parametric correlation method statistically. It demonstrated coefficientr=0,435 with p value=0,037. It is concluded that increasing number of prominent nucleolushepatocytes related to enhancing level of SREBP-1c in the process of T2DM towardsHepatocellular Carcinoma.